2021
DOI: 10.3390/molecules26102861
|View full text |Cite
|
Sign up to set email alerts
|

α-Terpineol: An Aggregation Pheromone in Optatus palmaris (Coleoptera: Curculionidae) (Pascoe, 1889) Enhanced by Its Host-Plant Volatiles

Abstract: The Annonaceae fruits weevil (Optatus palmaris) causes high losses to the soursop production in Mexico. Damage occurs when larvae and adults feed on the fruits; however, there is limited research about control strategies against this pest. However, pheromones provide a high potential management scheme for this curculio. Thus, this research characterized the behavior and volatile production of O. palmaris in response to their feeding habits. Olfactometry assays established preference by weevils to volatiles pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the comparison of the attraction values of the binary and tertiary mixtures showed that the tertiary mixture was significantly more attractive to male and female weevils than the binary mixture (t < 0.05). Also, the preference percentages obtained from the tertiary mixture were comparable to those obtained from soursop slices supplemented with α-terpineol and males feeding on soursop fruits [15]. Nevertheless, it is important to conduct more laboratory and field experiments, with larger insect groups, to determine a final attractant product for Annonaceae fruit weevils.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Moreover, the comparison of the attraction values of the binary and tertiary mixtures showed that the tertiary mixture was significantly more attractive to male and female weevils than the binary mixture (t < 0.05). Also, the preference percentages obtained from the tertiary mixture were comparable to those obtained from soursop slices supplemented with α-terpineol and males feeding on soursop fruits [15]. Nevertheless, it is important to conduct more laboratory and field experiments, with larger insect groups, to determine a final attractant product for Annonaceae fruit weevils.…”
Section: Resultsmentioning
confidence: 67%
“…For instance, in a previous study, the role of α-terpineol as an aggregation pheromone was proven in the management of this Annonaceae fruit weevil. Moreover, in the same study, the whole bouquet of soursop volatiles was demonstrated to enhance the attraction effects of α-terpineol to this curculio [15]. Nevertheless, specific volatile compounds in the aroma of soursop were not identified or correlated with the attraction effects over these weevils.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Alongside these main streams of natural products research, two multidisciplinary investigations were reported: a study on natural products formulation with ionic liquids that are known as promising green media, Kiyonga et al [ 15 ] and a chemical ecology study related to pheromones by Pineda-Rios [ 16 ].…”
mentioning
confidence: 99%